1996
DOI: 10.1080/09670269600651411
|View full text |Cite
|
Sign up to set email alerts
|

The uptake of organic compounds byDunaliella parvaCCAP 19/9

Abstract: The feasibility of growing the unicellular green microalga DunaJielJa parva beterotrophically was investigated. D. parva cells were shown to take up [14C]glycerol and [~4C]glucose; the rate of uptake was fastest under illuminated conditions (photon flux density of 5 10 #tool m -2 s -1 ), but a significant rate of uptake was maintained in the dark for at least 6 h. The uptake of both compounds was stopped when photosynthesis and respiration were inhibited by adding carbonylcyanide m-chlorophenyl hydrazone (CCCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…( 1971 ) found that transport of glycerol by the bacteria, Pseudomonas aeruginosa, involves a binding protein responsible for recognition of glycerol. Additionally, studies with Dunaliella parva (Hard & Gilmour, 1996 ) showed that the uptake of glycerol is active, they confirmed the energy dependence of the glycerol transport system by its response to external salinity. These inconsistent results suggest that further investigations of glycerol transport in microalgae are warranted.…”
Section: Discussionmentioning
confidence: 80%
“…( 1971 ) found that transport of glycerol by the bacteria, Pseudomonas aeruginosa, involves a binding protein responsible for recognition of glycerol. Additionally, studies with Dunaliella parva (Hard & Gilmour, 1996 ) showed that the uptake of glycerol is active, they confirmed the energy dependence of the glycerol transport system by its response to external salinity. These inconsistent results suggest that further investigations of glycerol transport in microalgae are warranted.…”
Section: Discussionmentioning
confidence: 80%
“…as reported by Calixto et al (2016). While, it was reported that Dunaliella parva is able to grow heterotrophically utilizing glucose as an organic C-substrate for its growth (Hard & Gilmour, 1996).…”
Section: Resultsmentioning
confidence: 56%
“…Dunaliella salina CCAP 19/30 was supplied by the Culture Collection of Algae and Protozoa (CCAP), Oban, UK. The growth medium for Dunaliella, developed by Hard and Gilmour (1996), was used. Approximately 200 mL of freshly subcultured D. salina cells was added to the reactor until an initial optical density of 0.068 at 595 nm was achieved.…”
Section: Growth Of Dunaliella Salinamentioning
confidence: 99%